Milk protein suspensions enriched with three essential minerals: Physicochemical characterization and aggregation induced by a novel enzymatic pool - Lombardi, Julia (2015)
Fil: Fil: Lombardi, Julia. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas; Argentina.